The Psychometric Properties of the Persian Migraine-Specific Quality of Life Questionnaire Version 2.1 in Episodic and Chronic Migraines - Alireza Zandifar; Samaneh Sadat Masjedi; Faraidoon Haghdoost; Fatemeh Asgari; Navid Manouchehri; Mahboobeh Banihashemi; Mohammad Reza Najafi; Abbas Ghorbani; Behzad Zolfaghari; Ali Gholamrezaei; Vahid Shaygannejad; Mohammad Saadatnia (The Scientific World Journal)
Background. Migraine-specific quality of life (MSQ) is a valid and reliable questionnaire. Linguistic validation of Persian MSQ questionnaire, analysis of psychometric properties between chronic and episodic migraine patients, and capability of MSQ to differentiate between chronic and episodic migraines were the aims of this study. Method. Participants were selected from four different neurology clinics that were diagnosed as chronic or episodic migraine patients. Baseline data included information from MSQ v. 2.1, MIGSEV, SF-36, and symptoms questionnaire. At the third week from the baseline, participants filled out MSQ and MIGSEV. Internal consistency (Cronbach alpha) and test-retest reproducibility (intraclass correlation coefficients) were used to assess reliability. Convergent and discriminant validities were also assessed. Results. A total of 106 participants were enrolled. Internal consistencies of MSQ among all patients, chronic and episodic migraines, were 0.92, 0.91, and 0.92, respectively. Test-retest correlation of MSQ dimensions between visits 1 and 2 varied from 0.41 to 0.50. Convergent, item discriminant, and discriminant validities were approved. In all visits MSQ scores were lower in chronic migraine than episodic migraine; however, the difference was not statistically significant. Conclusion. Persian translation of MSQ is consistent with original version of MSQ in terms of psychometric properties in both chronic and episodic migraine patients.